An annotated list of the flora of the projected reserve «Staroshvedskyi» (Kherson region, Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The planned botanical nature reserve of local importance “Staroshvedskyi” is located in the area of the Zmiivka and Chervonyi Maiak councils, Beryslav District, Kherson Region, Ukraine. The proposed name of the reserve is associated with the existence of a Swedish colony here since the end of the XVIII century. The reserve planned to be built on an area of 263 hectares, including two ravines (so called ‘balkas’: Kostyrska and Shyroka) and a 3,5 kilometers long Dniepro river terrace. The territory is characterized by a wide variety of natural conditions. In addition to dominant steppe habitats, there are also meadows, scrublands, forest plantations and ruderal habitats, outcrops of limestone, loess and clay, limestone cliffs, and the Dniepro Reservoir. A list of the flora of the planned botanical nature reserve “Staroshvedskyi” includes 359 species of vascular plants, which belong to 222 genera, 68 families, 3 classes and 2 divisions. A good representation and a range of natives (279 species, 77.7%), steppe (171 species, 44.8%) and non-synanthropic plants (123 species, 34.2%) indicate a hight level of preservation of the object. The projected reserve shows a high conservation value at the regional, national and international level: ten plant species are included in the Red List of Kherson Province (Amygdalus nana, Bellevalia sarmatica, Bromopsis heterophylla, Ephedra distachya, Hyacinthella leucophaea, Jurinea stoechadifolia, Poa sterilis, Quercus robur, Vinca herbacea and Vitis sylvestris), ten plant species are included in the Red Data Book of Ukraine (Astragalus dasyanthus, A. ponticus, Elytrigia stipifolia, Ornithogalum boucheanum, Stipa capillata, S. lessingiana, S. pulcherrima, S. ucrainica, Tulipa biebersteiniana and T. gesneriana), and six vegetation communities are included in the Green Data Book of Ukraine (Amygdaleta nanae, Elytrigieta stipifoliae, Stipeta capillatae, Stipeta lessingianae, Stipeta pulcherrimae, Stipeta ucrainicae). Furthemore, one species (Jurinea cyanoides) and a range of habitats are covered by the Resolution № 4 to the Bern Convention (E1.2. Perennial calcareous grassland and basic steppes and F3.247 Ponto-Sarmatic deciduous thickets), and by the EU Habitats Directive. Taking the above into account, there is an urgent need to establish the botanical nature reserve of local importance “Staroshvedskyi”.
Keywords: vascular plants, rare communities, habitats, steppe, conservation.